CONSIDERACIONES EN TORNO A LA TRADUCCIÓN JURÍDICA, JURADA Y JUDICIAL - PETRESCU, Olivia Narcisa (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Considerations on Legal, Sworn and Court Translation. This paper departs from the premise that translation represents a type of intercultural communication, reflecting on the different systems of law in order to depict the characteristics of legal language (mainly in Spanish), comparing Common Law and Civil Law. After analyzing the functionality of legal texts and their compared translations into Spanish and Romanian, we deduce that there is a close link between the legal language that derives from each culture and the society from which it originates. Conceptual differences and similarities between legal, sworn and judicial translation are also explored, with the aim of finding elements that can support the interpretation of legal value and wider related areas, which must respect the requirements of form and content. Moreover, we discuss the legal load in the source and target text, in accordance with written, oral and other specific factors to legal language. Some complex translation issues arising from semantic, lexical, syntactic, phraseological, formal and generic difficulties are also touched upon. Last but not least, we aim to highlight some typologies of legal texts, according to their role, mode, tone, genre, effect, which also implies a practical delimitation of legal, sworn and Court translation. Considerații privind traducerea juridică, autorizată și judiciară. Această lucrare pleacă de la premisa că traducerea este o formă de comunicare interculturală, reflectând asupra diferitelor sisteme de drept pentru a ajunge la caracteristicile limbajului juridic (în principiu în limba spaniolă), comparând Common Law și Dreptul Civil. După analiza funcționalității textelor legale și a comparației între traducerilor lor în spaniolă și română, deducem că există o legătură strânsă între limbajul juridic ce caracterizează fiecare cultură și societatea din care provine. De asemenea, se studiază diferențele și asemănările conceptuale între traducerea juridică, autorizată și judiciară, cu scopul de a găsi elemente care pot sprijini interpretarea valorii legale și a altor domenii conexe mai ample, aspecte care trebuie să respecte exigențele legate de formă și de conținut. În același timp, se discută încărcătura juridică din textul sursă și din textul țintă, în concordanță cu factorii nivelului scris, oral și cu alții specifici limbajului juridic. Totodată, se ating unele chestiuni complexe de traducere ce decurg din dificultăți semantice, lexicale, sintactice, frazeologice, formale și generice. În final, ne propunem să evidențiem câteva tipologii ale textelor juridice, în funcție de rolul, modul, tonul, genul, efectul lor, ceea ce implică și o delimitare practică a traducerilor juridice, autorizate și judiciare. Cuvinte-cheie: traducere, comunicare interculturală, traducerea juridică, traducerea autorizată, traducerea judiciară Article history: Received 02 October 2023; Revised 31 December 2023; Accepted 21 January 2024; Available online 27 March 2024; Available print 27 March 2024